Negotiating Sharia in Secular State: A Case Study in French and Germany - Zada, Khamami; Irfan, M. Nurul (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2021)
The European Muslims, the majority of them come from Muslim countries, are facing the identity dilemma. On the one hand, they are the Muslims who are obliged to carry out their religious teaching, but on the other hand, they are the Muslims who have acquired European citizenship who cannot enforce religious laws and instead submit to secular state laws. The study analyzes French and Germany Muslim aspirations and their negotiations on carrying out sharia in the secular state. This is field study by qualitative approach. Primary data was collected by interviews with Muslims of Moroccan, Tunisian, Algerian, and Turkish descent living in France and Germany. The study found that French and German Muslims want to apply sharia, but France and Germany do not allow religious law to be made a state law. These have left French and German Muslims to negotiate without opposition, resistance, and conflict. As European citizens, they accept secular law without losing their religious and social identity, though couldn’t fully implement Sharia.